Liquidity risk : empirical results from Tokyo Stock Exchange - Chen, Gaston Zhenghong (2008)
Liquidity is examined as a risk factor affecting stock returns in the Japan stock market by using an extended version of the Fama-French characteristic-based model. We find evidence to show that liquidity risk is present and significant in this market, and is priced. Liquidity risk is correlated with other well-known risk factors like size, book-to-market and momentum, but is still individually important in explaining cross-sectional variations in price. The presence of non-zero regression intercepts indicates that there are still other factors unaccounted for which are not included in the model.